STUDY OF TRAUMA ON ASTHI W.S.R TO ASTHIBHAGNA - Varinder Kaur,; Subhash Upadhyay,; Sakshi, (International Journal of Ayurveda and Pharma Research, 2021)
Ayurvedic science is being popularized worldwide. It has established history for the management of Bhagna in Sushruta Samhita. Ayurvedic philosophy is specific pertaining to the body constitution. The human body is composed of Dhatus. “Asthi” Dhatu is one of the main Dhatu in human body. “Asthi” is hard substance which remains even after most part of body has been decayed. Ayurvedic science has established history of trauma to Asthi (Asthibhagna). Ayurveda has aimed high for maintaining normal structure and function of deformed bones. It is high time to re-establish it by adopting proper research and methodology. The skeletal injuries are important incidences in human beings and they demand immediate management. The branch of science that deals with deformities of bones is known as Orthopedics, aimed for “maintenance of normal structure and function of deformed bones.” While bones are very strong they can break. Most often, breaks happen because the bone runs into a strong force, also repetitive force like from running can fracture a bone. High energy trauma result in bone fractures whether it is isolated fracture or dislocation. When a person goes through some form of trauma, as car accident or fall, the impact may break or fracture the bone. The bone fracture may be the result of high force impact or a result of certain medical conditions that weaken the bones such as Osteoporosis. Fracture is properly termed pathologic fracture but not trauma.